The clove oil effect on faunting time and survival rate of Oreochromis niloticus - Elfrida Elfrida; Abdullah Munzir; Amelia Sriwahyuni Lubis (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2023)
To overcome excess residues and fish mortality rates during transportation, natural ingredients, namely clove oil, can be used. Compounds in clove oil are considered safe because they use natural ingredients. The purpose of this study was to determine the effectiveness of using clove oil as an anesthetic agent with different doses on the length of time of unconsciousness and survival rate of tilapia. This research was conducted from May to June 2023. This research was carried out at the Bungus Fish Seed Center, Padang, and West Sumatera. The method used in this study is the experimental method. The design used in this study was a completely randomized design (CRD) consisting of 4 treatments and 3 replications. The treatment used in this study is use of clove oil with different doses. Treatment A1 = 0.5 ml L-1 water, A2 = 1 ml L-1 water, A3 = 1.5 ml L-1 water and A4 = 2 ml L-1 water. Observations of changes in tilapia behavior and water quality were analyzed descriptively, while the length of time of stupor and survival of tilapia obtained during the study were analyzed using analysis of variance (ANOVA). To see the differences between treatments, the Duncant Multiple Range Test (DMNRT) was performed. Data is processed using the SPSS 26 program. The conclusion that can be considered in this study is that the administration of clove oil with different doses as an anesthetic has a significant effect on the longest induction time, on the length of time the fish were unconscious, the length of time the fish regained consciousness and survival rate of tilapia. In treatment A2 with a dose of 1 mL L-1 of water, it was optimal to stun tilapia for 244 minutes with a survival of 88.89%.Keywords:Clove oilFish transportationTilapia